A Systematic Review of Voice Encryption Techniques for Secure Audio Transmission (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
As voice communication via digital networks becomes more and more common, protecting the integrity and secrecy of audio communications has become crucial. In order to protect recorded and live audio data from eavesdropping, manipulation, and unwanted access, this systematic review investigates and assesses a number of voice encryption methods. The study examines the efficacy of encryption techniques in terms of security strength, computing cost, latency, and resistance to cryptographic assaults, classifying them into time-domain, frequency-domain, hybrid, and machine learning-based approaches. Lightweight encryption techniques that work well in resource-constrained settings, including embedded and mobile systems, are given particular consideration. The paper also emphasizes new developments in adaptive and quantum-resistant voice encryption methods. This book serves as a thorough reference for researchers and practitioners interested in creating reliable and effective speech encryption systems by combining recent developments, difficulties, and prospective study directions.